The use of vitamin "C" as antioxidant to decrease lesions of atherosclerosis that induced experimentally by hydrogen peroxide in rabbits: D.S.Diab , B.S.Toma , K.K.Khudiar - Diab, D. S. (The Iraqi Journal of Veterinary Medicine, 2005)
This study was designed to investigate the effect of vitamin C inalleviating the changes in lipid profile and the atherosclerotic lesions inducedexperimentally by (0.5%) H2O2 in drinking water. Twenty four adult malesrabbits were divided randomly into four equal (a control and 3 treated "T")groups for 19 weeks: 1- The Control group: Which was given normal drinkingwater. 2- Group (T1): was given 0.5% H 2O2 in drinking water. 3- Group(T2): which was handled as T1, in addition to vitamin C (100 mg /kg/day) alongthe experiment. 4- Group (T3): was treated as T1 till the atherosclerotic lesionswere established at the week 13, then the animals received 100 mg/kg of vitaminC daily for 6 weeks. Blood samples were taken at the weeks 5, 13, 16 and 19 ofthe experimental period to measure the levels of total cholesterol (TC),triglycerid (TG), HDL-C, LDL-C and VLDL-C in plasma. Samples of aortictissue were taken to study the histopatholpgical changes. The results showed thatH2O2 caused an increase in TC, TG, LDL, VLDL-C and a decrease in HDL-Cconcentration in plasma. The histopathological sections showed lesions ofatherosclerosis in the aorta as fatty streaks and foam cells. Moreover, resultsshowed that treatment with vitamin C caused a dereased in the VLDL-C, LDLC,TG and TC levels and an increase in the HDL-C concentration in plasma. andregression of atherosclerotic lesions. Results of the present study suggest that theoxidative stress (produced by 0.5% H2O2) has an important role in pathogenesisof atherosclerosis in the rabbits and vitamin C has an important effect inreducing and preventing some of the oxidative stress changes in lipid profile andatherosclerotic lesions of the aorta. It is worthed to report that this is the firststudy undertaken in using vitamin C as an antioxidant to minimize the oxidativestress effects of H2O2 in rabbits as a model for atherosclerosis in mammals.